COVID-19, the Brain, and the Future: Is Infection by the Novel Coronavirus a Harbinger of Neurodegeneration? - Onaolapo, Adejoke; Onaolapo, Olakunle (CNS & Neurological Disorders - Drug Targets, 2022)
The possible impact of viral infections on the development or pathogenesis of neurodegenerative disorders remains largely unknown. However, there have been reports associating the influenza virus pandemic and long-term infection with the Japanese encephalitis virus with the development of post-encephalitic Parkinsonism or von Economo’s encephalitis. In the last couple of years, there has been a worldwide pandemic caused by the novel coronavirus or severe acute respiratory syndrome coronavirus (SARS-CoV)-2, which causes a severe acute respiratory syndrome and is found to be associated with symptoms or complications of the central nervous system. Its possible involvement with the central nervous system is in line with emerging scientific evidence stating that the human respiratory coronaviruses can enter the brain, infect neural cells, persist in the brain, and cause activation of myelin-reactive T cells. Currently, there is a dearth of scientific information on the acute or possible long-term impact of infection with SARS-CoV-2 on the development of dementia and/or neurodegenerative diseases. This is related to the fact that the virus is ‘new,’ and its effects on humans are still being studied. This narrative review examines the extant literature for understanding the impact of coronavirus infections on the brain as there is a possibility that coronavirus disease 2019 (COVID-19) could increase the risk for the development of neurodegenerative diseases or hasten their progression.
Keywords: neurodegeneration